Determination of Hydrolyzed Tannin Content in Cocoa Fruit Peel Waste of MCC 01 Clone, Using UV-Vis Spectrophotometry - Yessika D. Mangela; Baharuddin Hamzah; Sitti Rahmawati; Sri H. V. Pulukadang (Jurnal Akademika Kimia, 2025)
Cocoa Fruit Peel Waste MCC 01 Clone (Theobroma cacao L.) is a traditional medicinal plant with tannins that can be utilized as an anti-bacterial because it contains phenol groups and has antiseptic properties. This study aims to determine the type of tannin compound and the tannin content in cocoa fruit peel waste extract. The maceration method was used to extract the extract using 70% ethanol as a solvent. Qualitative test of tannin type was conducted using C2H4O2 10%, C2H3O2 10%, HCl, FeCl3, and KBr, while quantitative test was conducted using UV-Vis Spectrophotometry at a wavelength of 765 nm. The qualitative test results to determine the type of tannins obtained from cocoa fruit peel waste indicate that it contains hydrolyzed tannins. In the quantitative test, the average tannin content was 4.73 mg/g extract.